The sugar coated bitter pills - Jawaid, Shaukat Ali (Karachi, Professional Medical Publications, 1993)
The Sugar-Coated Bitter Pill explores the hidden complexities and ethical dilemmas within modern medicine and the pharmaceutical industry. The book examines how healthcare practices, drugs, and treatments are often presented in a favorable (3z(Bsugar-coated(3y (Bway, while underlying risks, side effects, or ethical concerns remain underemphasized. Through critical analysis, case studies, and real-life examples, it highlights the need for transparency, informed decision-making, and ethical responsibility in medicine. This work is intended for healthcare professionals, policymakers, and general readers interested in the social and moral aspects of healthcare.s
DC011225
English.
Keywords: Medical journalism; Medicine -- Press coverage; Medical ethics; Physicians -- Professional ethics; Medicine -- Social aspects; Public health -- Pakistan